Consumer Protection against AI-Induced Skin Care Misdiagnosis in Skin Health Services in Indonesia - alif farhan; Andry Setiawan Setiawan (Universitas Negeri Semarang, 2026)
The development of Artificial Intelligence (AI) in the beauty industry has led to the innovation of electronic-based skin diagnostic services, one of which is AI in Skin Health Services. While offering convenience and personalized product recommendations, the use of this technology poses the risk of misdiagnosis that could potentially harm consumers. This study addresses two main issues: how to protect consumers from misdiagnosis by AI in Skin Health Services in Indonesia and the legal liability of business actors for the resulting losses. The research method used is normative legal research with a statutory and conceptual approach, through an analysis of provisions in the Consumer Protection Law, the Electronic Information and Transactions Law, and regulations related to electronic systems. The results show that AI in Skin Health Services can be qualified as an electronic service and system, thus making business actors responsible based on the principle of presumption of liability with a tendency towards strict liability to ensure protection and legal certainty for consumers.